Accidental displacement of the third lower molar impacted towards the lateral pharyngeal space - Del Águila del Castillo, Queneth (2010)
An unusual accident of displacement of the third lower molar towards the left lateral pharyngeal space was reported in a 21-year old female patient, located through the tomographic exam. In order to remove the dental piece, local anesthesia was used (2 % of lidocaine with epinephrine 1:100 000). An incision was made from the distal of the 3,7 piece continuing by the alveolar ridge up to the coronoid process, and through a blunt dissection the dental piece was found, the same that was grasped and then removed with haemostatic clamps. It was concluded that valuation of the potential complexity regarding the dental extraction of the third molars must be made; and that moderate and high-complexity cases must be derived to the specialist to avoid complications.